2017
DOI: 10.1038/nchembio.2528
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of highly potent and selective allosteric USP7 inhibitors

Abstract: Given the importance of ubiquitin-specific protease 7 (USP7) in oncogenic pathways, identification of USP7 inhibitors has attracted considerable interest. Despite substantial efforts, however, the development of validated deubiquitinase (DUB) inhibitors that exhibit drug-like properties and a well-defined mechanism of action has proven particularly challenging. In this article, we describe the identification, optimization and detailed characterization of highly potent (IC < 10 nM), selective USP7 inhibitors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(196 citation statements)
references
References 53 publications
3
188
0
Order By: Relevance
“…A serious of inhibitors targeting USP7 was evaluated in vitro and in vivo studies . In which, P5091 was identified as a specific inhibitor of USP7 and showed a promising anti‐cancer effect in several tumors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A serious of inhibitors targeting USP7 was evaluated in vitro and in vivo studies . In which, P5091 was identified as a specific inhibitor of USP7 and showed a promising anti‐cancer effect in several tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Several inhibitors targeting USP7/HAUSP were screened and exhibited anti‐tumor effect . Chauhan et al discovered that P5091 exhibited specific and selective deubiquitylating activity against USP7 and did not inhibit other DUBs.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50] One interesting example was reported by Ernst et al [51] where directed evolution was used to generate ar ange of Ub variants (Ubvs) that selectively target their corresponding DUBs. [48][49][50] One interesting example was reported by Ernst et al [51] where directed evolution was used to generate ar ange of Ub variants (Ubvs) that selectively target their corresponding DUBs.…”
Section: With Lt-b To Du145 and Hela Cells A) 3 (Green) In Du145 Celmentioning
confidence: 99%
“…Through this platform, specific UbVs have been identified that can inhibit USP7 and USP10 with high affinity . Implementation of fragment‐based methods and surface plasmon resonance (SPR) has led to the generation of new compounds with high inhibition potency . Combination of features of published USP7 inhibitors and binding fragments has resulted in Compound 1 as exemplified by t7‐Bromo‐3‐((4‐hydroxy‐1‐(3‐phenylpropanoyl)piperidin‐4‐yl)methyl)thieno[3,2‐d]pyrimidin‐4(3H)‐one (IC 50 13.1 μM) which is later developed to generate the potent compound 4 (IC 50 6 nM).…”
Section: Ubiquitin Specific Protease 7 (Usp7)mentioning
confidence: 99%